Estudo de um PIBID interdisciplinar organizado a partir da metodologia de problematização e da abordagem CTS - Santos, Érica de Souza (2015)
Teacher education has been a major challenge for governments and policy of our country, especially in recent decades. Economic globalization, new technologies and the development of alternative sources of information, collaborate, among other factors, to some significant changes in society and education.For thar reason, the great demand for teacher with appopiate qualifications has become morevisible on one side,on the other side, the difficulty of improving the conditions of teaching and learning and preparing the professionals for the educational practice challenges. Thus, this research aims at analyzing an interdisciplinary PIBID developed at the University of Franca (SP), with students who attend the graduate coure in science. The project was organized through the problematization methodology and the STS approach and was applied in two public school in the city of Franca. The methodology of this study was bibliographical and ethnographic survery to increase the knowledge of the sudy. After that, a survey of descriptive field with questionnaires and interviews with participants was carried out. The results were compared to other PIBIDs studies, considering positive features of the programme.